STATUS HUKUM DARAH REPRODUKSI PEREMPUAN (ANALISIS INTEGRATIF ANTARA PENDEKATAN NORMATIF DAN KEDOKTERAN TERHADAP KETIDAKTERATURAN MENSTRUASI PADA AKSEPTOR KB) - Wahyu Setiawan (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
One of the effects of hormonal contraceptive in family planning  (KB) acceptors is the irregularity of the menstrual cycle. Changes in menstrual patterns due to progesterone contraceptive system generally in the form of change and cycle time, and spoting events (incidence of blood spots are irregular and sometimes prolonged). These  changes can  occur  over 15 days. So that raises  a problem of provision between menstrual blood  status (haidh) or istihâdhah. The purpose of this article  is to discuss  the  reality of the  menstrual cycle  changes  for acceptors of family planning (KB) and trying to find legal status of reproductive blood as applicable legal product. This articles hows  that the incidence of spoting should  be seen in terms  of the timing of the spoting. If bleeding occurs before  menstrual blood  every month, it is not judged  as menstruation but istihâdhah. If spoting  occurs after normal  bleeding, then see the normal  number of days of bleeding and spoting itself. If spoting events  that accompany normal  bleeding exceeds fifteen days, then spotting after fifteen days specified as istihâdhah